'The other side of the net': (re)presentations of (emphasised) femininity during Wimbledon 2016. Issue 2 (4th May 2018) - Domeneghetti, Roger
ABSTRACT: This article examines how the British Popular Press articulated notions of femininity during the 2016 Wimbledon Championships. Copies of the Daily Mail and The Sun and their sister Sunday papers were collected during the tournament and subsequently analysed using textual analysis (McKee, 2001) and drawing on Connell's neo-Gramscian concept of gender power relations (1987, 2000, 2002, 2005) for theoretical insight. The analysis suggests that although the women's and men's competitions were held concurrently and female tennis players gained a greater share of the overall coverage (when compared to their male counterparts) than female athletes in other sports, long-standing gendered discursive strategies were still evidenced within the reportage of the tournament. In particular, the media image of white female players, and the white partners of male players, was constructed in accordance with traditional subordinate, passive and sexualised roles. At the same time, black female tennis players were cast in the role of 'other' through their representation as extra-ordinary 'superwomen'.